Collapsed carbon nanotubes: From nano to mesoscale via density functional theory-based tight-binding objective molecular modeling. (March 2019) - Xu, Hao; Drozdov, Grigorii; Hourahine, Ben; Park, Jin Gyu; Sweat, Rebekah; Frauenheim, Thomas; Dumitrică, Traian
Abstract: Due to the inherent spatial and temporal limitations of atomistic modeling and the lack of efficient mesoscopic models, mesoscale simulation methods for guiding the development of super strong lightweight material systems comprising collapsed carbon nanotubes (CNTs) are currently missing. Here we establish a path for deriving ultra-coarse-grained mesoscopic distinct element method (mDEM) models directly from the quantum mechanical representation of a collapsed CNT. Atomistic calculations based on density functional-based tight-binding (DFTB) extended with Lennard-Jones interactions allow for the identification of the cross-section and elastic constants of an elastic beam idealization of a collapsed CNT. Application of the DFTB quantum treatment is possible due to the simplification in the number of atoms introduced by accounting for the helical and angular symmetries exhibited by twisted and bent CNTs. The multiscale modeling chain established here is suitable for deriving ultra-coarse-grained mesoscopic models for a variety of microscopic filaments presenting complex interatomic bondings. Graphical abstract: